Flat pneumatic elements and their potential use in the construction of dwelling facilities within emergency housing systems - Szymański, Witold (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2021)
As part of this study, experimental and theoretical investigations into the strength and stiffness of flat pneumatic elements to be used in lightweight dwelling structures, enabling the quick assembly of the latter, were undertaken. On the basis of the experimentally and theoretically determined parameters of the elements it will be possible to design configurations of spatial pneumatic structures. In particular, the following were devised and carried out: a theoretical assessment of the load capacity and stiffness of selected pneumatic elements depending on their dimensions, internal pressure and fixing and support conditions, an experimental verification of the obtained results. This study has an exploratory character and constitutes the basis for the design and implementation of original technical, constructional and architectural solutions relating to the application of spatial pneumatic structures in the emergency system. It should be mentioned that in the known literature on the subject there is no theoretical basis for designing structures whose principal member is a flat pneumatic element. In the construction industry such structures have not been used so far. An exemplary solution of the spatial dwelling structure has been patented under the name Obiekt mieszkalny (Dwelling facility), (patent no. 131 528, of 18.04.1988).